Pengaruh Pemberdayaan, Komitmen Organisasional terhadap Kinerja dan Kepuasan Kerja Dosen (Persepsi Dosen Dipekerjakan PTS Kopertis Wilayah IX Sulawesi di Makassar) - Nongkeng, Hasan (Universitas Brawijaya, Indonesia, 2012)
This study aims to test and prove empirically: Theoretically, the results of this study is expected toenrich knowledge in the field of human resources, especially the theory of empowerment lecturer, so it canbe useful for academics and practitioners. Population of the study was the private university lecturersemployed in Universitas Veteran Repulik Indonesia, Universitas Muslim Indonesia, UniversitasMuhammadiyah dan Universitas 45 at Coordination of Private Higher Education Region IX of Sulawesi atMakassar, The sample of this research was155 lecturers from the total number of the population which was268 lecturers. The samples were taken by random sampling. The data were collected by giving questionner,interviewing and doing observation. Then the data were analyzed by the statistical results of researchthrough Structural Equation Model (SEM) with AMOS program. The results of this study indicate that: (1)the empowerment of the lecturers influences on the organizational commitment, so the commitment will beincreased; (2) the empowerment of the lecturers influences the performance of the lecturers, if the empowermentis increased, the performance will be increased, too; (3) the organizational commitment does notinfluence the performance of the lecturers, even though the commitment has been increased, it will not beincreased; (4) the performance of the lecturers influences the lecturers'job satisfaction, so the job satisfactionwill be increased; (5) the empowerment influences indirectly toward the performance through theorganizational commitment; (6) the empowerment influences indirectly toward the job satisfaction throughthe performance of the lecturers; and (7) the organizational commitment does not influence directly towardthe job satisfaction through the performance of the lecturers.